Hubungan Berat Badan Lahir Rendah, Pemberian Asi Eksklusif, Paparan Asap Rokok dengan Pneumonia Berat Pada Balita di RSUD Patut Patuh Patju Lombok Barat - Richa Baqiyatush Sholihah; Dian Rahadianti; Ananta Fittonia Benvenuto; Risky Irawan Putra Priono (MAHESA : Malahayati Health Student Journal, 2025)
ABSTARCT Pneumonia is an acute lung tissue infection caused by bacterial, viral and fungal infections. Pneumonia is still one of the main infectious diseases and causes of morbidity and mortality that attacks many toddlers in Indonesia. This study aims to determine LBW, exclusive breastfeeding, and exposure to cigarette smoke with severe pneumonia in toddlers at Patut Patuh Patju Hospital, West Lombok. This study used a cross-sectional design and focused on quantitative observational analysis. The results of the study showed that between LBW and severe pneumonia in toddlers based on the results of bivariate analysis using the chi-square test on 100 respondents, a p-value of 0.005 was found. Between the incidence of severe pneumonia in toddlers and exclusive breastfeeding, based on the results of bivariate analysis with the chi-square test, a p-value of 0.003 was obtained. Between exposure to cigarette smoke and severe pneumonia in toddlers, the p-value was 0.000. There is a statistically significant relationship between low birth weight, exclusive breastfeeding, and exposure to cigarette smoke with the incidence of severe pneumonia in toddlers.  Keywords: Pneumonia, Exclusive Breastfeeding, BBLR, Exposure to Cigarette Smoke.  ABSTRAK Pneumonia merupakan infeksi jaringan paru-paru yang bersifat akut, penyebabnya adalah infeksi dari bakteri virus dan jamur. Pneumonia masih menjadi salah satu penyakit infeksi dan penyebab kesakitan dan kematian utama yang banyak menyerang balita di Indonesia. Penelitian ini bertujuan untuk mengetahui BBLR, pemberian ASI eksklusif, dan paparan asap rokok dengan pneumonia berat pada balita di RSUD Patut Patuh Patju Lombok Barat. Penelitian ini menggunakan desain cross sectional dan berfokus pada analisis observasional kuantitatif. Hasil penelitian menunjukan antara BBLR dengan pneumonia berat pada balita berdasarkan hasil analisis bivariat menggunakan uji chi square pada 100 responden ditemukan hasil p-value 0,005. Antara kejadian pneumonia berat pada balita dengan pemberian ASI eksklusif, berdasarkan hasil analisis bivariat dengan uji chi-square diperoleh nilai p-value sebesar 0,003. Antara paparan asap rokok dengan pneumonia berat pada balita p-value sebesar 0,000. Terdapat hubungan yang signifikan secara statistik antara berat badan lahir rendah, pemberian ASI eksklusif, dan  paparan asap rokok dengan kejadian pneumonia berat pada balita.  Kata Kunci: Pneumonia berat, ASI Eksklusif, BBLR, Paparan Asap Rokok